Activation of the Cerebellum by Sensory Finger Stimulation and by Finger Opposition Movements - Nitschke, M F; Hahn, C; Melchert, U H; Heinz Handels; Wessel, K (Journal of neuroimaging : official journal of the American Society of Neuroimaging, 1998)
Activation of the ipsilateral anterior lobe of the cerebellum by means of hand movements by humans is a well-known phenomenon, but the cerebellar encoding of sensory information has not been well established. The authors delineated the representation of sensory stimulation of fingers in the anterior lobe of the cerebellum using functional magnetic resonance imaging sensitized to changes in blood oxygenation and compared these areas to the regions activated by means of finger opposition movements. Activation was determined by means of pixel-by-pixel correlation of the signal intensity time course with a reference waveform equivalent to the stimulus protocol. All subjects showed significant activation of the anterior lobe of the cerebellum, mainly located in the ipsilateral Larsell lobules IV-V and less consistent in the vermis in relation to sensory finger stimulation. Among some subjects the authors also found activation in the anterior lobe on the contralateral side. The finger movements activated regions that overlapped with the areas activated by sensory finger stimulation but showing a larger and more intense activation pattern.
Keywords: Adult; Afferent Pathways; Brain Mapping; Cerebellum; Dominance, Cerebral; Female; Fingers; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Motor Neurons; Motor Skills; Reference Values; Sensory Receptor Cells; Synaptic Transmission